Impact Evaluation of Three Types of Early Childhood Development Interventions in Cambodia - Bouguen, Adrien (The World Bank, 2013)
Scaling up early childhood development services has the potential to increase children's cognitive and socio-emotional development and promote school readiness in a large segment of the population. This study used a randomized controlled trial approach to evaluate three scaled-up programs designed to widen access to early childhood development services: formal preschools, community preschools, and home-based services. The impacts of all three programs fell short of expectations because of two key flaws in how they were scaled up. First, implementation did not receive due attention; as a result, school facilities were not completed as planned, community-based programs were not always established, and low, irregular stipends created difficulties in hiring and retaining teachers. Second, the services that were available were not promoted and thus not used as widely as anticipated. The results imply that the quality of programs supplied is critical, as is attention to the demand side of the problem. The finding that these programs fell short of expectations does not mean that interventions such as these are ineffective. Rather, it indicates that quality and demand require careful attention in attempts to scale up early childhood development interventions, and any problems should be addressed prior to evaluating effectiveness